A new 4-node quadrilateral element based on layerwise approach for free vibration analysis of laminate-faced sandwich plates - Mohamed-Ouejdi Belarbi; Abdelouahab Tati; Abdelhak Khechai; Houdayfa Ounis (Journal of Applied Engineering Science and Technology, 2016)
The new quadrilateral element based on the layerwise approach, developed earlier bythe present authors for the static analysis of laminated composite and sandwich plates, isextended to study the free vibration behavior of multilayer sandwich plates. The model is based onthe third order shear deformation theory for the core and the first order shear deformation theoryfor the face sheets. Compatibility conditions are imposed at face sheets/core interfaces to satisfythe interlaminar displacement continuity. Unlike the majority of the layerwise models, the numberof DOFs is independent of the number of layers. In order to study the free vibration, a consistentmass matrix is adopted in the present formulation. The obtained numerical results by the presentmodel are in excellent agreement with those obtained via analytical solution and numerical resultsfound in the literature.